Assessment generator for selective topics in O'Level mathematics - Nant Hnin Ei Cho (2013)
Educations become powerful and strengthen in every part of the world. It also becomes a measure to benchmark the development of many nations in today society. Singapore is known to have one of the most world-leading education systems. With this education system in Singapore, students are facing a high level of challenge in the society to achieve the level of mastery. Teaching and learning become inadequate to compete with the society. Self-assessment and self-practice become a necessity factor to boost up the learning process.